Exploring the possibilities of sustainable chinese cemetery in urban area - Denan, Zuraini; Sum, Wen Yun (Ocerint Publishing, 2021)
In urban cities space for the living is often hard to find, not to mention the dead. In many major urban municipalities, the older cemeteries which were initially considered to be large often run out of space for new burials and vacant land is scarce to extend for cemetery purposes or to develop as new cemeteries. Rapid urbanization in towns and cities has led to a challenge for suitable location. A liveable city must not only care for the wellbeing of the living, but both the living and the dead. With a growing population, the issue should not be taken lightly as it could become a potential threat to urban area in accommodating sufficient burial spaces in the near future. Chinese people do not have a unified religion, therefore, the traditional view of funeral and funeral customs are based on the combined influences of three religions, Order of Confucianism, Natural Law of Taoism and Reincarnation of Buddhism. Death can be comprehended as reincarnation, entering an eternal wonderland, or enter to an unknown world. People refuse to accept and admit death, therefore any religion or knowledge that could help and conquer the contradiction of life and death will be naturally adopted. The problem is whether the existing burial ground in the city can cater for future needs are still questionable. The issue is studied in planning perspective, institutional perspective, environmental perspective, socio-cultural perspective and religion perspective. The aim of the research is to rethink death as a whole in term of religions, cultures, rituals, traditions, practices, perception and value to re-create a meaningful, ecological and sustainable alternative for the care of the deceased and reconnect the living and the dead with nature. It is recommended that future Chinese burial ground to be more multifunctional in order to maintain its sustainability. Ash scattered and ground burial is the most preferred burial methods, while columbarium is becoming more common in Malaysia. Combination of varies preferred methods of burial can help to reduce sole dependent on ground burial where land in the city has becoming scarce and expensive.